WIND ENERGY POTENTIAL OF GUNUNG KIDUL COASTAL AS A FUNCTION OF PROBABILITY DISTRIBUTION - PH, Hendro; Setiawan, Ahmad Agus; Widyaparaga, Adhika (Master in Systems Engineering, 2015)
Gunung Kidul coastal is an area that has varying heights up to 250 meters above sea level, and dealing directly with the Indian Ocean. Based on the location of the height of the sea surface, with Logarithmic formulation of wind speed, Gunung Kidul coastal has a varying energy class. The method used is an analytical model of constant density atmospheric, assuming that the density of the air from sea level to the top of the atmosphere has a fixed value. Furthermore, the value of wind speed is used as a probability distribution function based on the data period of 24.5 years. The results of the average value of wind energy are grouped according to energy class. On the use of the Poisson probability distribution, the class of potential good of energy is reached at a height of over 450 meters above sea level. While the use of the Normal distribution and Weibull reach potential class good at 100 meters above sea level.